Essential Oils from Côa Valley Lamiaceae Species: Cytotoxicity and Antiproliferative Effect on Glioblastoma Cells - Mário Pedro Marques; Beatriz Guapo Neves; Carla Varela; Mónica Zuzarte; Ana Cristina Gonçalves; Maria Inês Dias; Joana S. Amaral; Lillian Barros; Mariana Magalhães; Célia Cabral (MDPI AG, 2023)
Lavandula pedunculata (Mill.) Cav., Mentha cervina L. and Thymus mastichina (L.) L. subsp. mastichina are representative species of the Côa Valley's flora, a Portuguese UNESCO World Heritage Site. L. pedunculata and T. mastichina are traditionally used to preserve olives and to aromatize bonfires on Saint John's Eve, while M. cervina is mainly used as a spice for river fish dishes. Despite their traditional uses, these aromatic plants are still undervalued, and literature regarding their bioactivity, especially anticancer, is scarce. In this work, the morphology of secretory structures was assessed by scanning electron microscopy (SEM), and the composition of essential oils (EOs) was characterized by gas chromatography-mass spectrometry (GC-MS). The study proceeded with cytotoxic evaluation of EOs in tumor and non-tumor cells with the cell death mechanism explored in glioblastoma (GB) cells. L. pedunculata EO presented the most pronounced cytotoxic/antiproliferative activity against tumor cells, with moderate cytotoxicity against non-tumor cells. Whereas, M. cervina EO exhibited a slightly lower cytotoxic effect against tumor cells and did not affect the viability of non-tumor cells. Meanwhile, T. mastichina EO did not induce a strong cytotoxic effect against GB cells. L. pedunculata and M. cervina EOs lead to cell death by inducing apoptosis in a dose-dependent manner. The present study suggests that L. pedunculata and M. cervina EOs have a strong cytotoxic and antiproliferative potential to be further studied as efficient antitumor agents.